Making Medical Decisions for Children with Profound Cognitive Disabilities: Pluralism and the Best Interest Standard - Randall, Pierce (The Hastings Center report, 2026)
Requests by parents or other caregivers for treatment to prolong the lives of minors with profound cognitive disabilities can be ethically challenging. Some patients have very limited capacity for conscious experience, and so it becomes difficult to say that a longer life is truly good for them. For such cases, some commentators have proposed the relational potential standard as an alternative to the best interest standard. Yet, if the relational potential standard holds that requests for care ought to be honored because they respect patients’ familial relationships even though they provide no benefit to patients themselves, then the proposal is objectionable. We have good ethical reasons to accept at least one element of the best interest standard: the exclusionary criteria that no one's interests but the patient's should count when making medical decisions on their behalf. This paper defends a pluralistic conception of what can be in a severely cognitively disabled minor patient's interests. This approach can yield the same result that proponents of the relational potential standard want (honoring requests for care even when providers doubt that these requests are in the patient's best interest) while avoiding committing clinicians to honoring unreasonable requests that discount the patient's other interests.